Therapy of Postoperative Pain in Ambulatory Dental Practice (Texas Journal of Medical Science, 2022)
An integral part of postoperative pain therapy is adequate. Widespread use of NSAIDs - the modern trend of postoperative analgesia. A large number of study to assess the efficacy and safety of ketorolac (ketorol) and nimesulide (Niza).